Comparative Study Of Islamic Education Models In Public And Private Universities - Akyuni, Qurrata; Nurainiah, Nurainiah; Zulfadli, Zulfadli (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
Islamic Religious Education (PAI) in Indonesia plays a very important role in the formation of character and religious values for students. This study aims to analyze the differences in Islamic education models at public and private universities. With a qualitative approach, this research collects data through interviews, observations, and document studies at several universities in Indonesia. The research results show significant differences between public and private universities in terms of curriculum, teaching methods, and learning outcomes. In public universities, the curriculum is more focused on the development of academic knowledge integrated with religious values, whereas in private universities, the Islamic education approach tends to emphasize strengthening religious practices and the spiritual character of students. The teaching methods at public universities tend to use a more theoretical approach, while private universities often employ practical approaches and interactive discussions. The learning outcomes also show differences in the reinforcement of religious understanding and the implementation of Islamic values in daily life. These findings are expected to contribute to the development of Islamic education in Indonesia by adapting educational models that align with the needs and characteristics of students in each type of higher education institution.